Green Software Engineering Exploring Green Technology for Sustainable IT Solutions - Fontanarrosa, Santiago; Fontanarrosa, Santiago (Packt Publishing, 2024)
Craft sustainable software and reduce digital environmental impact with practical strategies and principles Key FeaturesDiscover practical strategies for developing energy-efficient digital solutions across various domainsLearn effective strategies to measure and mitigate the environmental impact of digital solutionsExplore real-world examples of integrating sustainable design patterns into the software development cyclePurchase of the print or Kindle book includes a free PDF eBookBook DescriptionEmbark on a transformative journey toward sustainable software engineering, exploring the vital intersection of technology and environmental responsibility. Authored by Santiago Fontanarrosa, a Green Software Foundation member with 20+ years in software engineering, this book explores practical strategies and use cases to help you assess and mitigate digital product environmental impact. Through real-world examples and hands-on experiences, you$1 (Bll gain the skills you need to craft environmentally responsible solutions aligned with green software engineering principles. As you progress, you$1 (Bll assess and optimize software architecture for sustainability within a sustainable software delivery framework schema. Beyond technical insights, the book delves into ethical implications and societal impacts, fostering a deeper understanding of the broader implications of technology usage. As you approach the conclusion, you$1 (Bll have gained the ability to comprehend, measure, and craft energy-efficient digital solutions aligned with green software engineering principles.What you will learnOptimize software and infrastructure for sustainabilityIntegrate green software principles into the Agile Software Development Life CycleExplore emerging trends and technologies shaping the future of green software engineeringReflect on tech ethics as well as address societal and environmental concernsImplement industry standards and reporting methodologies for software emissionsMeasure digital operations' environmental footprint with methodologiesMitigate software's ecological impact with strategic approachesWho this book is forIf you$1 (Bre a software developer, software architect, or IT professional who wants to integrate sustainability into your organization, this book is for you. Whether you're a seasoned professional or a sustainability-focused tech enthusiast, this book provides the knowledge and tools you need to drive positive change in the software industry. A basic understanding of IT concepts and programming is recommended, and familiarity in modern digital technologies like cloud computing will also be helpful.s